A decade with anomic primary progressive aphasia - Shoko Ota; Kazuo Kakinuma; Wataru Narita; Yoshiyuki Nishio; Nobuko Kawakami; Ayane Tamagake; Shigenori Kanno; Minoru Matsuda; Kyoko Suzuki (eNeurologicalSci)
Some patients with primary progressive aphasia (PPA) demonstrate only anomia. The lack of longitudinal observations of anomic PPA precluded us from determining whether progressive anomic aphasia was simply an early stage of semantic or logopenic variants, or a relatively independent variant. Herein, we report the 10-year clinical course of a patient with PPA who presented with pure anomic aphasia for 9 years. He is a right-handed man with anomia, who noticed word-finding difficulty at age 73. He was admitted to the hospital at age 77. On admission, the patient showed pure anomic aphasia with preserved other language function. Episodic memory and visuospatial function were preserved. Magnetic resonance imaging (MRI) revealed left temporal lobe atrophy. At 82 years of age, the patient presented with pure anomic aphasia. At 83 years old, he showed mild impairment in word comprehension and semantic memory, in addition to anomia. MRI demonstrated further atrophy in the bilateral anterior temporal lobes, predominantly on the left side. This case suggests the possibility of slowly progressive, late-onset anomic PPA, which could be differentiated from the early stage of semantic or logopenic variants.